Characterization of Toxoplasma gondii glyoxalase 1 and evaluation of inhibitory effects of curcumin on the enzyme and parasite cultures. Issue 1 (December 2015) - Goo, Youn-Kyoung; Yamagishi, Junya; Ueno, Akio; Terkawi, Mohamad; Aboge, Gabriel; Kwak, Dongmi; Hong, Yeonchul; Chung, Dong-Il; Igarashi, Makoto; Nishikawa, Yoshifumi; Xuan, Xuenan
Abstract Background The glyoxalase pathway, which includes two enzymes, glyoxalase 1 and 2 (Glo1 and Glo2), is a ubiquitous cellular system responsible for the removal of cytotoxic methylglyoxal produced during glycolysis. Protozoan parasites, includingToxoplasma gondii (T. gondii ) tachyzoites, produce methylglyoxal because of increased glycolytic fluxes. A Glo1 inhibitor such as curcumin could be considered a drug candidate for anti-protozoan, anti-inflammatory, and anti-cancer therapy. Methods TheT. gondii Glo1 gene (TgGlo1) was cloned and the recombinant protein was produced. Enzyme kinetics of TgGlo1 and five mutants were evaluated by adding methylglyoxal and glutathione to a reaction mixture. Finally, the inhibitory effects of various concentrations of curcumin on recombinant TgGlo1 were evaluated using in vitro cultures ofT. gondii . Results Active recombinant TgGlo1 was successfully produced and the active sites (E166 and E251) of TgGlo1 were verified by point mutagenesis. Curcumin at the tested doses inhibited the enzymatic activity of recombinant TgGlo1 as well as the parasitic propagation of in vitro-culturedT. gondii . The Ki and IC50 were 12.9 ± 0.5 μM and 38.3 ± 0.9 μM, respectively. Conclusion The inhibitory effect of curcumin on the enzymatic activity of TgGlo1 and parasitic propagation ofT. gondii could be explored in the potential development of a potent drug for the treatment of toxoplasmosis. However, considering the fact that curcumin is known to have many effects on other molecules in the micromolar range, further elucidation of curcumin's direct inhibition of the glyoxalase system ofT. gondii will be needed.